2019
DOI: 10.1177/1744806919839860
|View full text |Cite
|
Sign up to set email alerts
|

Aging alters signaling properties in the mouse spinal dorsal horn

Abstract: A well-recognized relationship exists between aging and increased susceptibility to chronic pain conditions, underpinning the view that pain signaling pathways differ in aged individuals. Yet despite the higher prevalence of altered pain states among the elderly, the majority of preclinical work studying mechanisms of aberrant sensory processing are conducted in juvenile or young adult animals. This mismatch is especially true for electrophysiological studies where patch clamp recordings from aged tissue are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 76 publications
3
12
2
Order By: Relevance
“…This is on the basis of work from our group showing significant alterations in the electrophysiological properties of DH neurons that occur very early in postnatal development-either side of a critical developmental period from P6 to P10 (Walsh et al, 2009). In other work, we have shown there are subtle but significant changes in excitability, excitatory drive, and GABA signaling between young adulthood (3-4 months) and advanced age (28-32 months; Mayhew et al, 2019). Taken together, this supports the view our comparisons are unlikely to be influenced by animal age.…”
Section: Methodsmentioning
confidence: 63%
“…This is on the basis of work from our group showing significant alterations in the electrophysiological properties of DH neurons that occur very early in postnatal development-either side of a critical developmental period from P6 to P10 (Walsh et al, 2009). In other work, we have shown there are subtle but significant changes in excitability, excitatory drive, and GABA signaling between young adulthood (3-4 months) and advanced age (28-32 months; Mayhew et al, 2019). Taken together, this supports the view our comparisons are unlikely to be influenced by animal age.…”
Section: Methodsmentioning
confidence: 63%
“…Finally, the expression of some of the genes we assessed did not show any age-related change in our analysis, including neuroinflammatory and glial related proteins, and the majority of synaptic proteins. This was surprising for the dorsal spinal cord, as our previous work has identified alterations in synaptic function in these circuits with age 17 that predict altered gene expression. This discrepancy could be explained by incomplete translation of gene expression through to protein as suggested above.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, DH neurons exhibit a more excitable phenotype along with decreased spontaneous excitatory synaptic input, and an increased contribution of GABAergic signalling to inhibition. 17 While the ultimate outcome of these combined changes for sensory processing under normal and pathological conditions remains to be determined, collectively they confirm that the excitability and signalling in the aged dorsal horn differs from its younger counterpart.…”
Section: Introductionmentioning
confidence: 82%
“…Collectively, these results imply that age-related changes of PAG networks are implicated in defective pain control circuits in elderly. An interesting set of evidence demonstrated that dorsal horn neurons obtained from old mice exhibited faster action potential discharges, with a reduction of excitatory inputs allied to an increased GABAergic inhibitory signaling, in comparison with the younger ones, according to evaluation by patch clamp electrophysiology ( Mayhew et al, 2019 ). The authors suggested that aged spinal neurons might be more susceptible to injuries, helping to explain the altered pain transmission in the elderly.…”
Section: Pain Transmission and Experience In The Geriatric Populationmentioning
confidence: 99%